2018
DOI: 10.1001/jamanetworkopen.2018.2327
|View full text |Cite
|
Sign up to set email alerts
|

Association of Use of Omega-3 Polyunsaturated Fatty Acids With Changes in Severity of Anxiety Symptoms

Abstract: Key Points Question Is omega-3 polyunsaturated fatty acid treatment associated with an improvement in anxiety symptoms? Findings In this systematic review and meta-analysis of 19 clinical trials including 2240 participants from 11 countries, improvement in anxiety symptoms was associated with omega-3 polyunsaturated fatty acid treatment compared with controls in both placebo-controlled and non–placebo-controlled trials. The anxiolytic effects of omega-3 pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 80 publications
3
65
1
1
Order By: Relevance
“…The findings indicating lower odds of anxiety disorders for those with higher intakes of fruits and vegetables, as well as pulses and nuts, are consistent with the results of other studies [28][29][30]. Nuts may be protective against anxiety disorders because certain types, such as walnuts, are good sources of omega-3 fatty acids.…”
Section: Research Question 3: What Specific Dietary Intakes Are Assocsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings indicating lower odds of anxiety disorders for those with higher intakes of fruits and vegetables, as well as pulses and nuts, are consistent with the results of other studies [28][29][30]. Nuts may be protective against anxiety disorders because certain types, such as walnuts, are good sources of omega-3 fatty acids.…”
Section: Research Question 3: What Specific Dietary Intakes Are Assocsupporting
confidence: 90%
“…The findings indicating heightened odds of anxiety disorder with intakes of pastries are also consistent with the results of other studies [28,29]. Some investigations suggest that individuals with anxiety may self-pacify with sugary products as "comfort food" [65].…”
Section: Research Question 3: What Specific Dietary Intakes Are Assocsupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, in an experimental study, consumption of 3 g/day of EPA and DHA in patients with current obsessive-compulsive disorder reduced anxiety disorder [29]. Another experimental study reported that consumption of at least 2000 mg/day n-3 PUFAs in adults reduced anxiety disorder [30]. However, a meta-analysis did not show beneficial effects of omega-3 supplementation on the prevention of anxiety symptoms [31].…”
Section: Introductionmentioning
confidence: 99%
“…If this is so, then we should anticipate that a long-term exposure to such a dysbalance in essential PUFAs might trigger a critical state, and then only long term-reversal with high dosages would be able to act therapeutically. This has been actually shown in recent meta-analyses of therapeutic trials, which are surely only the beginning [18][19][20][21]. They do, however, point the way: in some patients, and perhaps we have to figure out first which ones they are, such nutritional interventions may actually be causal.…”
Section: Psychiatry Is Broadening the Biological Paradigm At Last -A mentioning
confidence: 93%